Communication as a tool for effective project execution at selected construction sites in Cape Town, South Africa - Zita, Tabile (Cape Peninsula University of Technology, 2020)
This study aims to establish the essence of communication as a tool for effective project execution at selected construction sites in Cape Town, South Africa. There is increasing evidence that communication practices can play a significant role in accomplishing high quality construction projects. Communication has been precisely singled out as a foremost construction project management practice that can have an effect on successful project execution. Failure to convey the proper messages results in projects delay or project failure as the employees or subordinates will not be given the right instructions on what to do. Most companies that are involved in construction projects around Cape Town are failing to complete their projects in the given time, budget and scope due to poor communication. The general objective of the study was to determine if effective communication could lead to the success of construction projects in Cape Town. The study implemented descriptive and association research designs while the study population was drawn from construction a large company within the vicinity of Cape Town. The study used simple random sampling technique while the sample size was 80 employees and 10 managers. The study used questionnaires to collect data while. An excel data analysis tool was used to analyze quantitative data while data was presented using geometric techniques such as tables, bar-graphs and pie charts. The results of the study exposed that the relationship between construction project success and effective communication was significant. The study recommended that construction project companies should have strong and effective communication techniques.
Thesis (MTech (Business Administration in Project Management))--Cape Peninsula University of Technology, 2020
Keywords: Resources; communication; dual loyalty; leadership prototype; organisational politics; communication barriers